Histomorphology of Fayoumi Species Embryo Effected by the Intake of Nicotine and Green Tea (Medical Forum Monthly, 2022)
Objective: The objective of this study is to consider how the nicotine consumption responsible of affecting the growth of avian species that is embryos of chick.Study Design: Randomized control studyPlace and Duration of Study: This study was conducted at the Quetta institute of Medical Sciences (NUMS), Islamabad for six month from June 2021 to November 2021.Materials and Methods: The study was designed and conducted with the collaboration of poultry research institute of Rawapindi (PRI). It is further supervised and conducted in the department of Anatomy of Quetta Institute of Medical sciences.(NUMS).The study was a randomized control in nature. Eggs of Fayoumi species were placed at the zero hour of incubation by dividing thirty eggs in three experimental groups. Ten eggs for group G1 was considered as a control group, experimental group G2, experimental group G3 and experimental group G4 all groups were injected with 0.1ml quantity of working solution through airsac at the blunt end of the eggs by the insulin guage needle. Fixation of specimen were done by placing them in the formalin filled jars at 17th day of incubation. Data analysis was done by using SPSS (Statistical Package for Social Science) version 25.Results: The results were calculated by calculating the CRL that is crown rump length, and comparing with the control group and with each other. Data were entered and analyzed using SPSS version 25. p value of less than 0.05 was considered significant.Conclusion: It was concluded that oxidative stress by nicotine causes the developmental growth defects of chick embryo. Whereas green tea minimizes the oxidative stress caused by nicotine.